A Circuit Model to an Encoche Coplanar Antenna for a Radio Frequency Identification TAG - Abdelhak Ferchichi; Ali Gharsallah (International Journal of Electrical and Computer Engineering (IJECE), 2013)
In this paper, Miniature Encoche Coplanar antennas are proposed. Tovalidate our structure and to develop an analytic method to determine thegeometry parameters, the Lumped theory is used. The proposed structure issimulated using ADS and then Compared to the electrical Model. Theproposed circuit has the same resonant aspect when comparing to theEncoche antenna with a much reduced simulation time. The compactcoplanar antenna has a box with a size of 36*52*0.2 mm3. This antenna willbe designed to an RFID TAG that resonates on 2.45 GHz.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2579